Moral courage and psychological empowerment among nurses - Zahra Khoshmehr; Maasoumeh Barkhordari-Sharifabad; Khadijeh Nasiriani; Hossein Fallahzadeh (BMC, 2020)
Abstract Background Moral courage is one of the fundamental values of nursing profession and a powerful method of coping with ethical problems. Psychological empowerment is a suitable method of enabling individuals to coping mental pressures of the work environment. This study determined the correlation between moral courage and psychological empowerment of nurses. Methods This was a descriptive cross-sectional study. A total of 180 nurses employed in different wards were selected randomly. Data were collected by Demographics Questionnaire, Sekerka's Moral Courage Scale, and Spreitzer's psychological empowerment Scale and analyzed with SPSS16 using descriptive and inferential statistics. Findings The results indicated that the mean score of moral courage was 21.11 ± 69.90 and the greatest amount of moral courage was in the dimension of "going beyond compliance". The mean score of "psychological empowerment" was 30.9 ± 73.58 and the greatest mean belonged to "competence". There was a positive significant correlation between "psychological empowerment" and "moral courage and its dimensions" (P < 0.05). Conclusion The findings suggested a correlation between moral courage and psychological empowerment. Thus, nurses' moral courage could be enhanced by reinforcing their psychological empowerment leading to increased patient satisfaction and quality care.